Early rehabilitative treatment after infrainguinal lower limb bypass surgery - Carlisi, Ettore; Caspani, Patrick; Morlino, Paola; Bardoni, Maria Teresa; Lisi, Claudio; Bejor, Maurizio; Dalla Toffola, Elena (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Functional activity may remain limited in patients affected by critical limb ischemia, despite successful infrainguinal lower limb bypass surgery (ILLBS). The aim of the work was to evaluate the impact of a rehabilitative intervention on postoperative ambulatory status and pain. Methods: In an observational study, data were collected on 34 patients undergoing ILLBS for critical limb ischemia or end-stage peripheral arterial disease. All patients underwent a postoperative rehabilitation program aimed at recovering gait autonomy. Information was collected on pre-operative comorbidities, ambulatory status (on admission to and discharge from hospital) and pain in the affected lower limb (on the first physiotherapy session and at discharge). Results: Before ILLBS, 61.8% of the patients walked independently without aids or assistance. The rehabilitative program started on average 5.7 (SD: 2.1) days after surgery. At discharge, 50% of the patients walked independently, 41.2% walked with aids and/or assistance and 8.8% were not able to walk. Overall, 76.5% of the sample recovered their pre-operative ambulatory status. Although pain tended to decrease, the difference at the first (1.5; SD: 2.6) and at the last treatment session (0.8; SD= 1.3) was not statistically significant. Conclusion: Our exercise protocol resulted to be easy to perform during hospital stay, with an overall favourable outcome for ambulatory status. Our results are in line with those reported in literature about the rates of postoperative dependence in walking, but appear to be slightly better in regards to the percentage of patients who recovered pre-operative ambulatory status.